Supply Chain Integration and Performance of Food and Beverages Manufacturing Firms in Kenya - Ngatia, Regina; Osoro, Anthony; Nyang’au, Samson (International Journal of Supply Chain Management, 2024)
Purpose: The major aim of this study was to analyze the effect of supply chain integration and performance of food and beverages manufacturing firms in Kenya. Methodology: The study adopted a cross-sectional survey. The target population was senior procurement managers from 246 food and beverage manufacturing firms in Kenya. A sample size of 150 respondents was determined using Krejcie and Morgan (1970). The sample was selected using simple random sampling. Pilot study of 10% of sample size was conducted consisting 15 firms and 13 questionnaires were returned. The researcher used semi-structured and self-administration questionnaires. 135 questionnaires were distributed to respondents but only 119 questionnaires were returned. Data analysis was done through descriptive statistics by use of mean, standard deviation, skewness and kurtosis. Inferential statistics was also done by use of correlation, regression and hypothesis testing. The data obtained was processed using SPSS version 28. Data was presented by use of tables. The reliability results indicates that all the variables meet the threshold of a Cronbach’s alpha value of above 0.7. Validity was also tested using content, construct and criterion. Results: Supply chain integration and performance of food and beverage manufacturing firms in Kenya had a significant and positive relationship (R2=.491, p =.000), according to the data. This meant that supply chain integration enhances performance of Kenyan food and beverage manufacturers. Supply chain integration and performance of food and beverage manufacturing firms in Kenya revealed a positive and statistically significant relationship (R2=.491), according to the study. As a result, supply chain integration accounted for 49.1 percent of the variation in food and beverage manufacturing firm’s performance. Unique Contribution to Theory, Practice and Policy: Process Theory may be used to anchor future studies in the manufacturing sector. The study recommended that managers of companies that manufacture food and beverages develop procedures and policies that link to a superior understanding of the client in order to meet their expectations, even though the existing theory was validated. The study suggests that regulators overseeing the food and beverage industry should develop policies that permit manufacturers to collaborate with third parties, thereby mitigating losses that could affect the productivity of these companies and ultimately the whole economy. According to the report, in order to improve performance, the government should ensure that supply chain integration in Kenyan food and beverage manufacturing companies grows and develops in a more methodical manner. Furthermore, in order to determine how supply chain integration affects the productivity of other manufacturing sectors in the economy, empirical study must be done.